Mengenali Teknik Pemecahan Masalah melalui Permainan Rantai Kertas - Studi Kasus Siswa Menengah Atas - Anatasia, Velly; Tannia, Tannia; Susilo, Sophia Reni; Siratan, Elkunny Dovir; Florencia, Livia Evangelina (Universitas Andi Djemma, 2025)
Education plays a crucial role in every individual's life, providing opportunities to acquire knowledge, develop skills, and shape attitudes. One essential aspect of education is how students cultivate leadership skills and actively participate in organizations. However, students often face various challenges while carrying out organizational tasks, and a lack of problem-solving skills can hinder their effectiveness. To address this issue, a community service activity was conducted to provide creative problem-solving training for students involved in school organizations. This training aimed to equip students with both the mental resilience and practical skills needed to handle problems, whether anticipated or unexpected. A total of 29 students from SMK Tarakanita South Jakarta participated in this experiential learning program. The learning approach used in this program was experiential learning, which emphasizes learning through direct experience. Additionally, the Participatory Rural Appraisal (PRA) approach was integrated into the activities. The evaluation results demonstrated a statistically significant improvement in the student's knowledge and behavior after participating in the paper chain game activity. The findings suggest that important life skills including problem-solving skills can be effectively taught from a young age using experiential learning methods. This article also discusses the program’s design, outcomes, and challenges encountered during implementation.